Infectious and mechanical complications in planned-start vs. urgent-start peritoneal dialysis: a cohort study - Müller, João Victor Costa [UNESP]; Ponce, Daniela [UNESP] (FapUNIFESP (SciELO), 2023)
Background: Few studies have compared the infectious and mechanical complications seen in planned-start and urgent-start peritoneal dialysis (PD) patients. Objectives: To compare the incidence and etiology of mechanical and infectious complications in patients offered planned- and urgent-start PD and assess potential differences in patient survival and time on PD. Methods: This retrospective cohort study included patients with chronic kidney disease on planned- and urgent-start PD seen from 2014 to 2020 and compared them for mechanical and infectious complications, clinical outcome, death rates, and need to switch to hemodialysis. Results: Ninety-nine patients on planned-start PD and 206 on urgent-start PD were included. Incidence of exit-site infection (18.9 vs. 17.17%, p=0.71) and peritonitis (24.27 vs. 27.27%, p=0.57) were similar between patients, while pathogens causing peritonitis were different, although non-fermenting Gram-negative bacilli were more commonly seen in the planned-start PD group. Leakage as a mechanical complication and hospitalization were more common among patients needing urgent-start PD (10.68 vs. 2.02%, p=0.0085 and 35.44 vs. 17.17%, p=0.0011, respectively). Patient survival was similar between groups. Cox regression found an association between death and age (HR=1.051, 95% CI 1.026-1.07, p=0.0001) and albumin (HR=0.66, 95% CI 0.501-0.893, p=0.0064), and between peritonitis and a diagnosis of diabetes (HR=2.016, 95% CI 1.25-3.25, p=0.004). Conclusion: Patient survival and time on PD were similar between the planned- and urgent-start PD groups, while leakage was more frequently seen in the urgent-start PD group. Death was associated with lower albumin levels and older age, while peritonitis was associated with diabetes.
Complicações infecciosas e mecânicas relacionadas à diálise peritoneal de início planejado vs. não planejado: um estudo de coorte
Keywords: Peritoneal Dialysis; Peritonitis; Renal Replacement Therapy